2021
DOI: 10.3390/molecules26092555
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity in Rheum emodi Wall (Himalayan Rhubarb)

Abstract: Using natural products as antioxidant agents has been beneficial to replace synthetic products. Efforts have been made to profile the antioxidant capacities of natural resources, such as medicinal plants. The polyphenol content of Himalayan rhubarb, Rheum emodi wall, was measured and the antioxidant activity was determined using DPPH and ABTS+ assay, and the oxidative stress was assessed using SOD enzymatic assay. Five different solvent fractions, n-hexane, n-butanol, ethyl acetate, dichloromethane, and water,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The quantity of TPC was calculated by a regression equation of a standard curve, y = 0.0009x + 0.1441, R 2 = 0.964, and ranged from 854.791 to 897.847 mg GPE per g of dry extract weight. The phenolic content in R. emodi water extract was higher than the n-butanol, ethyl acetate, n-hexane, dichloromethane, and water extracts reported by the study done by Park lee (Park & Lee, 2021). They reported that the lowest TPC is in the n-hexane extract of R. emodi was 27.76 mg GAE/g, while the highest amount is seen in ethyl acetate was 209.21 mg GAE/g.…”
Section: Resultsmentioning
confidence: 75%
“…The quantity of TPC was calculated by a regression equation of a standard curve, y = 0.0009x + 0.1441, R 2 = 0.964, and ranged from 854.791 to 897.847 mg GPE per g of dry extract weight. The phenolic content in R. emodi water extract was higher than the n-butanol, ethyl acetate, n-hexane, dichloromethane, and water extracts reported by the study done by Park lee (Park & Lee, 2021). They reported that the lowest TPC is in the n-hexane extract of R. emodi was 27.76 mg GAE/g, while the highest amount is seen in ethyl acetate was 209.21 mg GAE/g.…”
Section: Resultsmentioning
confidence: 75%
“…According to Park et al (2021) , the polyphenol contents and antioxidant activities of the ethyl acetate fraction were the greatest. It was chosen as an extraction solvent for further investigation into the identification of antioxidant compounds using HPLC with gradient elution.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1 shows that the samples were prepared following the method ( Park et al, 2021 ). The plant materials were air-dried, and 800 g of the sample were powdered and extracted with 70% ethanol under reflux (3×2.5 L, 2 h each time), then filtered through Whatman No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations